On the taxonomic identity and nomenclature of Cyperus megapotamicus (Cyperaceae) - de Moraes, Pedro L. R. [UNESP]; Sennikov, Alexander N. (Wiley, 2021)
Cyperus megapotamicus (A. Spreng.) Kunth is a nomenclatural synonym of Rhynchospora megapotamica (A. Spreng.) H. Pfeiff. but was originally misapplied to a species of Cyperus. Contrary to the rules, both species names are in current use in different genera. We here clarify the perpetuated taxonomic and nomenclatural confusion regarding the identity of C. megapotamicus sensu Kunth and related names and conclude that Cyperus jaeggii Boeckeler is the correct name to be adopted. We provide an amended circumscription of this species, with Cyperus mauryi Kuntze and Pycreus nematodes Schrad. ex C. B. Clarke as its newly proposed heterotypic synonyms. Additionally, lectotypes are designated for the names Scirpus megapotamicus A. Spreng., Rhynchospora maculata Maury, Rhynchospora luzuliformis var. elongata Kuntze, Rhynchospora luzuliformis var. subcapitata Kuntze, Cyperus jaeggii, Cyperus mauryi and Pycreus nematodes.
Keywords: Argentina; Bolivia; Brazil; Chile; Cypereae; Cyperoideae; Paraguay; Pycreus sect. Propinqui; Rhynchospora sect. Luzuliformes; Surinam; Uruguay